Characterization of Phosphate Rock of Garhi Habibullah, District Mansehra, Pakistan - Naseer M. Khan; Ishaq Ahmed; Sajjad Hussain; Imtiaz Ali (International Journal of Economic and Environmental Geology, 2018)
Phosphate rock is essential and basic raw material for fertilizer and chemical based industries. In this research work, characterization of Ghari Habibullah (GHU) phosphate rock samples, were carried out. Aim of the study is to determine mineralogy of the ore deposits by using thin sections, X-ray Diffraction (XRD) and Scanning Electron Microscope (SEM) techniques. Elemental composition was determined by X-ray Fluorescence (XRF), assay of ore minerals and various gangue minerals were determined by chemical analysis. Mineralogical study results showed that the major gangue minerals present with ore mineral (apatite) are silica, hematite and calcite. The SEM analysis revealed that apatite (fluorapatite) was sandwiched between silica and calcite. X-ray Fluorescence indicated apatite grade is 22.85% which is below the marketable cutoff grade and main gangues are quartz 40% and hematite grade greater >2% is more than the required limit of fertilizer. The iron content should be kept low in the fertilizers, reduces the solubility efficiency of water, which have a diverse effect on the production of Single Super Phosphate.